Gamma-ray and fast neutron shielding characteristics of inconel super alloys, stainless steel-304, and Pb using MCNPX, WinXCom, XMuDat, and Auto-Zeff software - Reza Bagheri; Hassan Ranjbar (Scientific Reports)
Abstract Fast neutron and gamma-ray attenuation characteristics of Inconel-600, -601, -625, and − 718 superalloys, stainless steel-304, and lead were studied using MCNPX Monte Carlo code, WinXCom, XMuDat, and Auto-Zeff computer programs. The µm, HVL, MFP, σa, σe, Zeff and Neff, and ΣT were calculated for 192Ir, 18F, 137Cs, and 60Co gamma sources and 1 MeV fast neutrons. The difference between the MCNPX and calculated results was less than ± 2%. Above and below 511 keV photon energy, respectively, Inconel-600 and Inconel-625 have the highest mass attenuation coefficient among Inconel alloys. The thickest HVL and MFP values were achieved for the Inconel-601 superalloy. The σa and σe values decreased as photon energy increased. The Zeff values were approximately constant with photon energy increase. The Zeff of the Inconel-601 was the lowest, while that of Inconel-625 was the highest. In the studied gamma-ray energies, the Neff value variations were insignificant. The stainless steel-304 material was found to have the highest ΣT, while Inconel-600 had the highest value between Inconel superalloys. Calculated data indicates that Inconel-600 is the superior candidate for shielding gamma rays among Inconel superalloys.